KEY MOTIVES OF CHILDHOOD IN ROALD DAHL'S WORKS - Narziyeva Inobat Zoirovna (Western European Studies, 2024)
This article gives us information about Roald Dahl's portrayal of childhood in his works. It highlights key themes such resilience, the power of the individual, the importance of friendship and family, and the darker side of childhood. Dahl's stories often transport readers to fantastical worlds, where children use their imagination to overcome challenges. They also showcase the resilience of young protagonists who face adversity with determination
Keywords: children's literature; childhood; imaginative